Index finger disability due to flexor superficialis tendon anomaly - Cugola, Landino; Fasolo, Gianpaolo; Canobbio, Luca; Testoni, Ruggero (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: We present the case of a 18 year old patient with history of two years of index disability, our purpose is to describe an atypical cause of digit dysfunction. Methods: An anomalous fibrous cord between the flexor superficialis tendon indicis and radius was found in a young man’s distal forearm upon surgical exploration after 2 years of index disability. Results: The excision of the fibrous cord resulted in quick and complete recovery. Conclusions: We offer our experience with this case in the differential diagnosis of digit disability. (www.actabiomedica.it)